The Fitzosbornes at war - Cooper, Michelle (New York Ember, 2012)
Sophie FitzOsborne and the royal family of Montmaray escaped their remote island home when the Nazis attacked. But now war has come to England--and the rest of the world. Even as bombs rain down on London, hope springs up in surprising places and love blooms. And when the Allies begin their drive across Europe, the FitzOsbornes take heart--maybe there will be a way to liberate Montmaray and go home at last.
Keywords: War stories -- Families -- Great Britain